Charting a new course: advancing maternal and neonatal health through collaborative innovation - Sreekanth Viswanathan (Maternal Health, Neonatology and Perinatology)
Abstract This article discusses the strategic vision and recent advancements of the Maternal Health, Neonatology, and Perinatology (MHNP) journal in promoting maternal and neonatal health. Emphasizing its alignment with the United Nations Sustainable Development Goals (SDG), particularly SDG3, the journal is committed to reducing maternal and neonatal mortality through rigorous peer-reviewed research. Implementation of our intelligent, AI-powered Reviewer Finder Tool within Snapp, Springer Nature’s next generation peer review platform, and a diverse editorial board enhance publication quality. The journal’s future goals include expanding its editorial team and focusing on emerging global health issues in maternal and neonatal health. By fostering collaborative innovation, MHNP aims to significantly impact maternal and neonatal health research and practice.